2022
DOI: 10.3390/microorganisms10122394
|View full text |Cite
|
Sign up to set email alerts
|

Euterpe oleracea Mart (Açaizeiro) from the Brazilian Amazon: A Novel Font of Fungi for Lipase Production

Abstract: Lipases (EC 3.1.1.3) are hydrolases that catalyze triglycerides hydrolysis in free fatty acids and glycerol. Among the microorganisms that produce lipolytic enzymes, the entophytic fungi stand out. We evaluated 32 fungi of different genera, Pestalotiopsis, Aspergillus, Trichoderma, Penicillium, Fusarium, Colletotrichum, Chaetomium, Mucor, Botryodiplodia, Xylaria, Curvularia, Neocosmospora and Verticillium, isolated from Euterpe oleracea Mart. (Açaizeiro) from the Brazilian Amazon for lipase activity. The prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…Additionally, there was an increase in fecal cholesterol excretion and enhanced expression of the LDL-R, 7α-hydroxylase, subfamily G transporters, and ATP-binding cassette genes in the rats [ 115 ]. These findings suggest that the consumption of açaí pulp positively effects diet-induced hypercholesterolemia by augmenting the expression of ATP-binding cassette, subfamily G transporters, and LDL-R genes [ 115 , 160 , 161 , 162 ]. Figure 10 shows an overview of antilipidemic effects of açaí.…”
Section: Biological and Pharmacological Effectsmentioning
confidence: 99%
“…Additionally, there was an increase in fecal cholesterol excretion and enhanced expression of the LDL-R, 7α-hydroxylase, subfamily G transporters, and ATP-binding cassette genes in the rats [ 115 ]. These findings suggest that the consumption of açaí pulp positively effects diet-induced hypercholesterolemia by augmenting the expression of ATP-binding cassette, subfamily G transporters, and LDL-R genes [ 115 , 160 , 161 , 162 ]. Figure 10 shows an overview of antilipidemic effects of açaí.…”
Section: Biological and Pharmacological Effectsmentioning
confidence: 99%
“…[Açaizeiro] A lipase activity was observed that exhibited the highest lipolytic activity in solid media [48] It is worth noting that various microbes in nature, particularly fungi and bacteria, can synthesize enzymes capable of biomass degradation. Cellulolytic microorganisms can evolve as individual degrading organisms or as part of a 'chain reaction' in microbial communities in some ecosystems.…”
Section: Cynodon Dactylonmentioning
confidence: 99%
“…(286 U/mL). On the other hand, Sena et al [74] obtained their extract with the highest lipase activity in 144 h using the endophytic fungus Aspergillus sp., which is closer in time taken to that obtained using E. endophytica QAT_7AC, although it presented lower enzyme activity. Thus, in order to reduce the cultivation time, there is a need to optimize the production of the fungal enzyme.…”
Section: Enzyme Productionmentioning
confidence: 99%
“…Thus, in order to reduce the cultivation time, there is a need to optimize the production of the fungal enzyme. Factors such as culture temperature and pH of the medium are crucial for lipolytic production [74] and were previously evaluated in the study by Matias et al [33]. However, other factors should be studied, such as agitation, components of the medium and inoculum concentration, in order to reduce the bioprocess time [33,75].…”
Section: Enzyme Productionmentioning
confidence: 99%